Cessation of cannabis use: A retrospective cohort study. (September 2019) - Seidel, Ann-Kathrin; Pedersen, Anya; Hanewinkel, Reiner; Morgenstern, Matthis
Highlights: No associations between cessation and age of onset, parental variables and prior drug use. Negative association for quality of first use and early increase of use. Preventive measures need to consider that trajectories of cannabis use are set early in life. Abstract: Given recent findings of a worldwide increase in cannabis use, a better understanding of the factors associated with cannabis use is needed. Most previous studies have focused on factors that predict the initiation of cannabis use, but less is known about factors associated with cessation. The present study is a retrospective cohort study of 6467 current or former cannabis users aged 15 to 46 years (mean age 22.5, SD  = 4.8). Data were collected via an online survey advertised in social media. All analyzed participants had used cannabis for at least three years. Approximately 16.3% ( n  = 1055) of the sample population had not used cannabis in the previous 12 months and were classified as quitters; all others (83.7%, n  = 5412) reported at least monthly use. Cessation was predicted by older current age, being female, nonmigrant status, less sensation seeking, using psychological treatment, more peer cannabis use during youth and more negative first experience with cannabis. An additional predictor was a nonincrease in the frequency of cannabis use in the first three years of use, indicating that trajectories of cannabis use are set early on and might be used to identify risk groups for early preventive measures.